Development of a new method to assess nanocrystal dissolution based on light scattering - Anhalt, Katharina; Harms, Meike; Fricker, Gert (Pharmaceutical research, 2012)
PURPOSE: Nanocrystals exhibit enhanced dissolution rates and can effectively increase the bioavailability of poorly water soluble drug substances. However, methods for in vitro characterization of dissolution are unavailable. The objective of this study was to develop an in situ noninvasive analytical method to measure dissolution of crystalline nanosuspensions based on light scattering. METHODS: Fenofibrate nanosuspensions were prepared by wet media milling. Their solubilities and dissolution profiles in simulated gastric fluid supplemented with 0.1% Tween(®) 80 were measured in a small scale setup with an instrument for dynamic light scattering and the intensity of scattered light as readout parameter. RESULTS: A good correlation was achieved between the dissolution profile of a nanosuspension measured in the light scattering setup and a conventional dissolution experiment. Nanosuspensions of 120-270 nm size could be distinguished by the light scattering method. The suspensions dissolved within 1.9-12.3 min. Over a concentration range of 40-87% of the solubility dissolution profiles of a nanosuspension with 140 nm were monitored and the determined total dissolution times were in good agreement with the Noyes-Whitney dissolution model. CONCLUSIONS: A noninvasive, sensitive and reproducible method is presented to assess nanocrystal dissolution. In situ measurements based on light scattering allow a straightforward experimental setup with high temporal resolution.
First Online: 12 June 2012
Gesehen am 15.06.2018